Influence of potato irradiation on its digestibility and nutritional value - Varela, G.; Moreiras-Varela, Olga (Ars Pharmaceutica (Internet), 1966)
A study is made in rats of the influence of radiation of potatoes en their digestibility and nutritive value. The potatoes employed were of the Alava variety and the dose of radiation was 8 Krad, sufficient to inhibit sprouting. Two lots of potatoes are studied comparatively, one treated, and the other used a control. The time elapsed from treatment of the beggining of the experiments was 43 days.